Jaideep Das
Jaideep Das, a tech industry professional, recalls how the Desi community in Silicon Valley found themselves needing access to books from India and how he was able to provide those services through his Bengali bookstore. He talks about the push that Silicon Valley gave him in starting his bookstore, as well as creating inclusive opportunities for kids to learn the Bengali language through his nonprofit organization called Dishari Foundation.